2007
DOI: 10.1111/j.1778-428x.2007.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative intravenous iron administration corrects anemia and reduces transfusion requirement in women undergoing abdominal hysterectomy

Abstract: SUMMARY We prospectively investigated the utility of preoperative intravenous (IV) iron treatment to increase hemoglobin (Hb) levels and reduce the need for transfusion in women with iron deficiency anemia (IDA) or iron deficiency (ID) scheduled for elective abdominal hysterectomy. Seventy‐five women with ID or IDA were enrolled in the study. Women having their surgical procedure at least 1 month after preoperative assessment received IV iron sucrose during 2–4 weeks (IV iron group, n = 31). Women having their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…Our results were in accordance with those previously published about the administration of iron sucrose in orthopedic and gynecologic patients 39,41,42 . However, data from a randomized controlled trial conducted by Edwards et al 43 .…”
Section: Intravenous Iron Replacement Therapysupporting
confidence: 93%
“…Our results were in accordance with those previously published about the administration of iron sucrose in orthopedic and gynecologic patients 39,41,42 . However, data from a randomized controlled trial conducted by Edwards et al 43 .…”
Section: Intravenous Iron Replacement Therapysupporting
confidence: 93%
“…Anemia impacts patients' quality of life and is associated with a variety of well‐recognized clinical consequences, including fatigue, low energy, exercise intolerance, decreased physical functioning, decreased vitality, feeling cold, reduced cognitive abilities, and cardiac dysfunction , as well as increased hospitalizations, blood transfusions, operative morbidity, and child and maternal mortality .…”
Section: Introductionmentioning
confidence: 99%
“…The iron dextran form, although demonstrating efficacy, resulted in an alarming rate of anaphylaxis, thereby precluding its use16. More recently, observational studies have shown a iron sucrose complex to reduce ABT and to correct anaemia following arthroplasty17, 18 and hysterectomy19.…”
Section: Introductionmentioning
confidence: 99%